A Novel Approach In Large Signal Power Line Communication - Nazem, Alireza (2014)
The main aim of this research is to identify and introduce a novel stand-alone and robust method for monitoring and control of a remote application. Among the three common techniques using fibre optic transmission layer, Supervisory Control And Data Acquisition (SCADA) and Power Line Communication (PLC). PLC method will result in minimizing the cabling usage. However, this technique will be unable to carry reliable information for long distance without the repeater facilities. In fibre-optic technique, although the attenuation of an optical transmission through a fibre layer is considerably low it will normally require additional electrical conductivity for transmission of power. Moreover, a hybrid cable, which consists of multiple physical fibre and copper layers, is irreparable in case of any damage during deployment and the cost of replacing such cables is often relatively high. While, A SCADA system will need both repeater facilities and additional power cable for remote applications. In order to overcome these problems, the Frequency and Amplitude Modulations Power Line Communication (FAMPLC) technique is proposed. FAMPLC, in general, provides a narrowband communication platform which consists of a Frequency Modulated Power Supply (FMPS) and Thevenin Equivalent Converter (TEC) block at the server side and the PWM reader and an active resistance as a dummy load at the receiver side. FMPS is a power gateway, as well as the large signal carrier for the Frequency Modulation (FM), to transmit the combination of the supplying voltage and the informative data as PWM.